Equilibrium Search with Time-Varying Unemployment Benefits - James Albrecht; Susan Vroman (Center for Economic Studies and ifo Institute (CESifo), 2001)
In this paper, we show how time-varying unemployment benefits can generate equilibrium wage dispersion in an economy in which identical firms post wages and homogeneous workers search for acceptable offers. We allow for matching frictions and for free entry and exit of vacancies, and we model time-varying unemployment benefits in a simple and natural way. We characterize the equilibrium, and we derive the comparative statics effects of changes in the unemployment compensation system on the equilibrium wage distribution and the unemployment rate.
Keywords: 330